Peran Teater Dala sebagai Wadah Pendidikan Karakter Mahasiswa Universitas Muhammadiyah Maumere - Albertina Rosdina Pero; Yosefa De Ancieta; Anastasia Yunianti; Rabita Isnanda; Petrus Kurniawan; Maria Ermilinda Dua Lering (Jurnal Ilmiah Dan Karya Mahasiswa, 2025)
Theater is a performing art that presents stories and ideas through collaboration between actors, directors and production crew. In theater, values ​​are depicted to shape character for both the audience and the performers in theatrical performing arts. Students who are members of the student activity unit or theater UKM will develop character when participating in theater UKM. This research is qualitative research which aims to describe the role of theater in forming student character. Data collection techniques were carried out using interviews. The results of the research are that theater has a very significant role in shaping the personal character of Muhammadiyah University Maumere students. This creative process forces students to think about looking for innovative solutions, and explore various ideas and ideas. This of course will improve critical thinking and problem solving skills which are much needed in various aspects of life. More than just forming character, theater is also an effective forum for developing students' self-expression. Acting as actors and actresses, students can express their emotions, ideas and views through the characters they play. Apart from that, participation in theater activities can also increase collaboration and teamwork among students. The theater production process involves many people with various skills and roles. Students learn to work together, respect each other's opinions, and compromise to achieve common goals.